Labour demand in Germany by industrial sector, occupational field and qualification until 2025 - model calculations using the IAB/INFORGE model - Maier, Tobias [Verfasser]; Mönnig, Anke [Verfasser]; Zika, Gerd [Verfasser] (My University, 2015)
"By means of a trend extrapolation of microcensus structures (undertaken by the German Federal Statistical Office) for the time period 1996-2007, the projections for labour demand by industrial sector which the IAB already has at its disposal can be transferred to demand by occupational field and subsequently by qualification level until 2025. The findings which have been claimed for some time now are upheld: production-related occupations will lose in significance, while further increases in employment particularly in occupations in the service sector are to be expected. Accordingly, the demand for personnel with a degree from a university or a university of applied sciences will go on rising, while the labour market opportunities for unskilled workers will continue to fall. However, vocational training or its academic counterparts still remain the dominant form of training in Germany. A continuing employment trend is to be expected here." (Authors' abstract, BIBB-Doku)
Keywords: G 1.2.1 Grund- & Strukturdaten des Arbeitsmarktes; S 6 Berufsbereiche; G 1.2.4 Wirtschaftszweige; T 3 Forschungsmethoden; Arbeitskräftebedarf; Berufsfeld; Wirtschaftszweig; Qualifikationsniveau; Modellierung; Projektion